Tal1, Gata2a, and Gata3 Have Distinct Functions in the Development of V2b and Cerebrospinal Fluid-Contacting KA Spinal Neurons - Andrzejczuk, Livia A.; Banerjee, Santanu; England, Samantha J.; Voufo, Christiane; Kamara, Kadiah; Lewis, Katharine E. (Frontiers in Neuroscience, 2018)
Vertebrate locomotor circuitry contains distinct classes of ventral spinal cord neurons which each have particular functional properties. While we know some of the genes expressed by each of these cell types, we do not yet know how several of these neurons are specified. Here, we investigate the functions of Tal1, Gata2a and Gata3 transcription factors in the development of two of these populations of neurons with important roles in locomotor circuitry: V2b neurons and cerebrospinal fluid-contacting Kolmer-Agduhr (KA) neurons (also called CSF-cNs). Our data provide the first demonstration, in any vertebrate, that Tal1 and Gata3 are required for correct development of KA and V2b neurons respectively. We also uncover differences in the genetic regulation of V2b cell development in zebrafish compared to mouse. In addition, we demonstrate that Sox1a and Sox1b are expressed by KA and V2b neurons in zebrafish, which differs from mouse, where Sox1 is expressed by V2c neurons. KA neurons can be divided into ventral KA’’ neurons and more dorsal KA’ neurons. Consistent with previous morpholino experiments, our mutant data suggest that Tal1 and Gata3 are required in KA’ but not KA’’ cells, whereas Gata2a is required in KA’’ but not KA’ cells, even though both of these cell types co-express all three of these transcription factors. In gata2a mutants, cells in the KA’’ region of the spinal cord lose expression of most KA’’ genes and there is an increase in the number of cells expressing V3 genes, suggesting that Gata2a is required to specify KA’’ and repress V3 fates in cells that normally develop into KA’’ neurons. On the other hand, our data suggest that Gata3 and Tal1 are both required for KA’ neurons to differentiate from progenitor cells. In the KA’ region of these mutants, cells no longer express KA’ markers and there is an increase in the number of mitotically-active cells. Finally, our data demonstrate that all three of these transcription factors are required for later stages of V2b neuron differentiation and that Gata2a and Tal1 have different functions in V2b development in zebrafish than in mouse.